White matter connectivity reductions in the pre‐clinical continuum of psychosis: A connectome study - Oestreich, Lena K. L. (Hum Brain Mapp, 2018)
Widespread white matter connectivity disruptions have commonly been reported in schizophrenia. However, it is questionable whether structural connectivity decline is specifically associated with schizophrenia or whether it extends along a continuum of psychosis into the healthy population. Elucidating brain structure changes associated with psychotic‐like experiences in healthy individuals is insofar important as it is a necessary first step towards our understanding of brain pathology preceding florid psychosis. High resolution, multishell diffusion‐weighted magnetic resonance images (MRI) were acquired from 89 healthy individuals. Whole‐brain white matter fibre tracking was performed to quantify the strength of white matter connections. Network‐based statistics were applied to white matter connections in a regression model in order to test for a linear relationship between streamline count and psychotic‐like experiences. A significant subnetwork was identified whereby streamline count declined with increasing psychotic‐like experiences. This network of structural connectivity reductions affected all cortical lobes, subcortical structures and the cerebellum and spanned along prominent association and commissural white matter pathways. A widespread network of linearly declining connectivity strength with increasing number of psychotic‐like experiences was identified in healthy individuals. This finding is in line with white matter connectivity reductions reported from early to chronic stages of schizophrenia and might therefore aid the development of tools to identify individuals at risk of transitioning to psychosis.